Training Stockmen in Animal Welfare-Based Slaughter Techniques to Reduce Bruising in Beef Carcasses - Wibowo, Ari; Suhardi; Mayulu, Hamdi; Aprylasari, Dede; Qamara, Cori; Gede Didik Widiarta, I Putu; Faisal Fanani, Anhar (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2024)
Animal welfare-based training on livestock handling techniques during sacrificial animal slaughtering is a crucial effort to reduce stress levels and bruising in cattle carcasses post-slaughter. This training, conducted at Al-Ma'ruf Mosque in Samarinda Ulu District, Samarinda City, involved 40 sacrificial animal handlers (stockmen) from various local mosques and prayer rooms. Participants were trained using the Rope Squeeze and Burley methods to enhance technical skills in livestock handling, particularly in reducing the risk of animal injury and work-related accidents. The training results demonstrated increased participants' understanding of livestock behavior and psychology and the application of the flight zone concept, contributing to safer and more effective livestock handling. The evaluation indicated the training's success in reducing livestock injuries and improving meat quality. Additionally, the training positively impacted the sacrificial animal slaughtering practices in the local area.